Analisis Penerapan PSAK 24 Mengenai Imbalan Pasca Kerja Pada PT Bank Negara Indonesia (Persero) Tbk - Dini Dwi Ermawati; Fani Yulia Rosyada (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research was conducted at a state-owned enterprise (SOE) operating in the financial sector, specifically in banking, namely PT Bank Negara Indonesia (Persero) Tbk, commonly referred to as BNI. The aim of this study is to examine the presentation and reporting of the implementation of PSAK 24 employee benefits, particularly post-employment benefits at PT Bank Negara Indonesia Tbk. The data used in this research is entirely secondary data, and the analytical technique employed is a descriptive quantitative method. The data used in this study includes the financial statements of PT Bank Negara Indonesia Tbk for the period 2020-2022. The data was collected from PT Bank Negara Indonesia Tbk and the official website of PT Bank Negara Indonesia Tbk. The results of the research at PT Bank Negara Indonesia Tbk indicate that the presentation and reporting of employee benefits are in accordance with PSAK 24. The employee benefits of PT Bank Negara Indonesia Tbk are recorded in the income statement, and in the statement of financial position, they are recorded as a liability account for employee benefits. The differences in the gains (losses) of employee benefits are recorded in the comprehensive income statement.